Ectomycorrhizal Fungi Associated With Pinus sylvestris var. mongolica Were Altered by Soil Environments With Aging Plantation in a Semi-arid Desert - Ren, Yue; Guo, Mishan; Ding, Guodong; Wang, Yue (Frontiers in Environmental Science, 2022)
Pinus sylvestris var. mongolica is a pioneer afforestation species for wind and sand fixation in northern China; however, most plantations have undergone unprecedented degradation since the early 1990s. Ectomycorrhizal (EM) fungi is the key to maintain host plant health and forest ecosystem function, and it is expected to be substantially related to the degradation of these plantations, because the life process of P. sylvestris depends on the assistance of it. Nevertheless, the direct evidence for this remains unclear. For this purpose, we investigated variation among EM fungal communities associated with P. sylvestris root samples of three age groups in Mu Us Desert. We found a total of 72 EM fungal taxa belonging to Basidiomycota (63) and Ascomycota (9). EM fungal community is highly enriched in Rhizopogon, Tuber, Tomentella and Inocybe, which mainly contribute to community differences. The diversity index and fungal species richness showed increasing trends towards the mature stand, but did not reach a significant level (P>0.05). The combination of soil physiochemical properties and soil enzyme activities jointly drive the variations of EM fungal community, but effect on them is not significant (P>0.05). We conclude that the major EM fungal group of P. sylvestris was strongly affected by soil environment with plantation ageing. Understanding the effects of environmental factors on the structuring of EM fungal communities could contributes to a firm basis for sustainable forest management in the future.